Testing brief intervention and phone contact among subjects with suicidal behavior: a randomized controlled trial in French Polynesia in the frames of the World Health Organization/Suicide Trends in At-Risk Territories study. Issue 2 (30th September 2015) - Amadéo, Stéphane; Rereao, Moerani; Malogne, Aurelia; Favro, Patrick; Nguyen, Ngoc Lam; Jehel, Louis; Milner, Allison; Kolves, Kairi; Leo, Diego De
Abstract : The World Health Organization Suicide trends in at-risk territories study is a multi-site regional research program operating first in French Polynesia and countries of the Western Pacific, then extended to the world. The aims of the study were to establish a monitoring system for suicidal behaviors and to conduct a randomised control trial intervention for non-fatal suicidal behaviors. The latter part is the purpose of the present article. Over the period 2008-2010, 515 patients were admitted at the Emergency Department of the Centre Hospitalier de Polynésie Française for suicidal behavior. Those then hospitalized in the Psychiatry Emergency Unit were asked to be involved in the study and randomly allocated to either Treatment As Usual (TAU) or TAU plus Brief Intervention and Contact (BIC), which provides a psycho-education session and a follow-up of 9 phone contacts over an 18-months period. One hundred persons were assigned to TAU, while 100 participants were allocated to the BIC group. At the end of the follow-up there were no significant differences between the two groups in terms of number of presentations to the hospital for repeated suicidal behaviors. Although the study could not demonstrate the superiority of a treatment over the other, nevertheless – given its importance – the investigation captured public attention and was able to contribute to the awareness of the need of suicide prevention in French Polynesia. The BIC model of intervention seemed to particularly suit the geographical and health care context of the country.